Pathobiochemical changes in liver and brain in experimental avian spirochaetosis - BANDOPADHYAY, A C; VEGAD, J L; QUADRI, M A (The Indian Journal of Animal Sciences, 2013)
Chicken infected with a virulent strain of Borrelia anserina manifested clinical, pathological and biochemical changes in liver, brain and scrum. Corresponding with spirochaetaemia, a widespread mononuclear infiltration, rapid mobilization of macrophages, erythropbagocytosis, haemosiderosis and presence of tissue spirochaetes characterized hy pathological changes in liver; while changes in brain were milder, delayed and inconstant, and were characterzed hy perivascular cuffing and gliosis. The infection altered the enzyme profile and the biochemical milieu by injuring cells and deranging protein biosynthesis.